2009
DOI: 10.1080/00016340902818170
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and maternal determinants of small‐for‐gestational age births: Patterns of increasing disparity

Abstract: Socioeconomic disadvantage remains one of the dominant determinants of SGA, even in a developed country with universal insurance. This relation appears to be strengthening. Smoking patterns, inadequate antenatal care and clinical conditions partially account for this association and trend, however, most is mediated by other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 25 publications
(28 reference statements)
3
43
0
1
Order By: Relevance
“…This study showed that the risk of intrauterine growth restriction increased with increasing socioeconomic disadvantage. A similar conclusion was drawn by Beard JR et al [4] in their study which stated that socioeconomic disadvantage remains one of the dominant determinants of SGA.…”
Section: Discussionsupporting
confidence: 84%
“…This study showed that the risk of intrauterine growth restriction increased with increasing socioeconomic disadvantage. A similar conclusion was drawn by Beard JR et al [4] in their study which stated that socioeconomic disadvantage remains one of the dominant determinants of SGA.…”
Section: Discussionsupporting
confidence: 84%
“…Several rodent studies have demonstrated significant changes in fetal body and brain composition, often in the absence of major reduction of birth weight following poor maternal nutrition during pregnancy (11,12). In relation to the changes in brain development that we report here in a nonhuman primate species, evidence is accumulating that birth weight at the lower end of the normal range is associated with impaired higher mental function in later life (5,13,14).We addressed effects of 30% global moderate MNR on early fetal cerebral development in a well-established nonhuman primate model, the fetal baboon. This degree of dietary reduction has beneficial effects on aging and life span in nonhuman primates (15) but may have adverse effects on brain development.…”
supporting
confidence: 58%
“…Recently, one study has shown that most women do not improve their dietary and lifestyle patterns in pregnancy (3). Decreased nutrient delivery to the fetus also occurs in teenage pregnancy (4) and during pregnancy in women over 35 y of age (5). Severe global reduction in nutrition during pregnancy has long been known to result in fetal growth restriction and to cause permanent brain dysfunction, especially cognitive and behavior deficits (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The variables found on the birth certificate data set, particularly tobacco use, were sufficient to explain all of the differences in SGA prevalence for mining counties with and without MTM mining activity and three-quarters of the difference among mining counties and non-mining counties. It may be that further inclusion of known risk factors for SGA, such as maternal height and weight [22] or socioeconomic disadvantage [23], might explain much of the remaining differences.…”
Section: Sga Prevalence By Mining Group Activitymentioning
confidence: 99%